Mums and their sons, dads and their daughters: panel data evidence of interdependent marginal utilities across 14 EU countries - José Alberto Molina; María Navarro; Ian Walker (Institute for the Study of Labor (IZA), 2007)
We study how fathers and mothers income satisfaction correlates with the income satisfaction of their sons and daughters, as well as with other economic and socio-demographic variables. We estimate these correlations using data on parents and children in households surveyed in the eight waves of the European Community Household Panel-ECHP (1994-2001) for 14 EU countries. To assess the robustness of these correlations, we use siblings in the Panel and we investigate the sensitivity of the estimates with the inclusion of other control variables. We also adopt a multi-level random effects ordered probit specification, that uses step-parents in the data, to allow us to distinguish nature effects from nurture effects. Our main results show evidence of strong altruism effects, but these estimated effects differ across countries, differ between mothers and fathers, and differ between sons and daughters.
urn:nbn:de:101:1-20080402404
Keywords: 330; Eltern; Kinder; Einkommen; Lebenszufriedenheit; Nutzen; Altruismus; EU-Staaten